(untitled) (European Journal of Pure and Applied Mathematics, 2011)
Introductory statistics education aims to train students to be efficient users, consumers or communicators of statistics. Building students’ conceptual understanding and statistical reasoning skills is essential for an introductory statistics course to be successful. Effective course curriculum must be developed to accommodate the facilitation and assessment of students’ retention of statistical knowledge learned. This paper presents a mixture of literature review and personal reflection on these issues in regard with introductory statistics teaching and learning.